Kecerdasan Moral Anak di Era Globalisasi Menurut Perspektif Imam Ghozali - Siti Ima Makhmudah (Universitas Muhammadiyah Surabaya, 2022)
AbstracEarly childhood is an age where all knowledge and development must begin to be stimulated. Knowledge as a source of world life and the hereafter. Children's moral education or better known as child morals will be perfect when using the correct religious order. One of the basic attitudes that must be possessed by children in order to have a good and right attitude is to have a good attitude, morals and religion as God's people. Therefore, a teacher in early childhood education must always try in various ways in order to be able to guide children to have a good personality that is based on moral and religious values. According to Imam Ghozali moral is the same as khuluq, which means morals. In his view, moral cultivation is better and more advisable from an early age. The purpose of moral education in the view of Imam Ghozali is to form a pure human soul in order to draw closer to Allah. The source of moral education according to Ghozali is revelation and through strict guidance through shaykh (teacher) so that it does not optimize the functioning of reason. Moral Ghozali's educational material is: the habituation method, the exemplary method, and the tazkiyah an-nafs (soul-cleansing) method. Therefore, a PAUD teacher must strive in various ways in order to be able to guide his students to achieve true moral intelligence in order to have a good personality. One of them is Imam Ghozali's understanding of early childhood moral intelligence that is widely known.Kerword : Intelligence Morals Analysis, Imam Ghozali Perspective, Early ChildhoodAbstrakAnak merupakan usia dimana semua pengetahuan dan perkembangan harus mulai di rangsangkan. Pengetahuan sebagai sumber kehidupan dunia dan akhirat. Pendidikan moral anak atau lebih dikenal dengan akhlak anak akan menuju sempurna apabila menggunakan tatanan agama yang benar. Salah satu sikap dasar yang harus dimiliki oleh anak agar mempunyai sikap yang baik dan benar adalah memiliki sikap, moral dan keagamaan yang baik sebagai umat Tuhan. Oleh karena itu seorang guru dalam pendidikan Anak harus selalu berupaya dalam berbagai cara agar dapat membimbing anak mempunyai kepribadian yang baik yang dilandasi dengan nilai moral dan agama. Menurut Imam Ghozali moral sama dengan khuluq, yang artinya akhlak. Dalam pandangannya, penanaman moral lebih baik dan lebih dianjurkan sejak usia dini. Tujuan pendidikan moral dalam pandangan Imam Ghozali adalah membentuk manusia yang suci jiwanya dalam rangka mendekatkan diri pada Allah. Sumber pendidikan moral menurut Ghozali adalah wahyu dan melalui bimbingan yang ketat melalui syaikh (guru) sehingga kurang mengoptimalkan fungsi akal. Materi pendidikan moral Ghozali adalah: metode pembiasaan, metode keteladanan, dan metode tazkiyah an-nafs (penyucian jiwa). Oleh karena itu seorang guru PAUD harus berupaya dengan berbagai cara agar dapat membimbing anak didiknya mencapai kecerdasan moral yang sebenar-benarnya agar mempunyai kepribadian yang baik. Salah satunya pemahaman imam Ghozali tentang kecerdasan moral Anak yang sudah banyak diketahui.Â